KUALITAS PELAYANAN PADA KAWASAN WISATA BENTENG KUTO BESAK PALEMBANG - Sabrina Sabila; Maya Damayanti (Diponegoro University, 2017)
Benteng Kuto Besak (BKB) that is located in the middle of Palembang is a tourism destination with the main attraction of heritage buildings. Given that, the local government is expecting this area as the main destination in Palembang, it is expected that this destination can provide services that can satisfy visitors. Hence, this research aims to assess the service quality based on visitor perceptionThis research used quantitative descriptive as the method in collecting and analysing data. The results show that the BKB as a whole has satisfied the visitors need, but there are still some services that need to be improved, such as the information and promotion.